Recent progress in the design, synthesis and applications of chiral metal-organic frameworks - Altaf, Amna; Hassan, Sadia; Pejcic, Bobby; Baig, Nadeem; Hussain, Zakir; Sohail, Manzar (Frontiers in Chemistry, 2022)
Chiral Metal-Organic Frameworks (CMOFs) are unique crystalline and porous class of materials which is composed of organic linkers and metal ions. CMOFs surpass traditional organic and inorganic porous materials because of their tunable shape, size, functional diversity, and selectivity. Specific applications of CMOFs may be exploited by introducing desired functional groups. CMOFs have chiral recognition abilities, making them unique for chiral compound synthesis and separation. The CMOFs can be synthesized through different approaches. Two main approaches have been discussed, i.e., direct and indirect synthesis. Synthetic strategies play an essential role in getting desired properties in MOFs. CMOFs find potential applications in adsorption, asymmetric catalysis, luminescence, degradation, and enantioselective separation. The MOFs’ porosity, stability, and reusability make them an attractive material for these applications. The plethora of applications of CMOFs have motivated chemists to synthesize novel MOFs and number of MOFs have been ever-escalating. Herein, the synthetic methods of CMOFs and their various applications have been discussed.